New Cosmopolitanisms, Race, and Ethnicity Cultural Perspectives - Luczak, Ewa Barbara (De Gruyter, 2019)
This anthology offers fresh perspectives on cosmopolitanism that reflect cultural challenges in the contemporary world. It demonstrates that new cosmopolitan thinking can be combined with a sensitivity to ethnic and local difference. Moreover, it argues that rather than clinging to the utopian notion of color-blind universalism, new cosmopolitan cultural practices should acknowledge the persistence of "race" in lived experience.